2018
DOI: 10.1039/c8nj02401d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of a mineral-substituted hydroxyapatite nanocomposite material for fluoride removal from drinking water

Abstract: Mineral substituted hydroxyapatite (mHAp) nanocomposite was synthesized and it shows high fluoride adsorption capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The values of Δ H ° were positive, which highlighted that the chromium adsorption was endothermic in nature. Furthermore, the positive values of Δ S ° indicated the good binding affinity of the synthesized adsorbents with chromium ions and increased randomness at the adsorbent–adsorbate interface during the adsorption process …”
Section: Resultsmentioning
confidence: 99%
“…The values of Δ H ° were positive, which highlighted that the chromium adsorption was endothermic in nature. Furthermore, the positive values of Δ S ° indicated the good binding affinity of the synthesized adsorbents with chromium ions and increased randomness at the adsorbent–adsorbate interface during the adsorption process …”
Section: Resultsmentioning
confidence: 99%
“…This can be additionally studied by the point of zero charge (pHzpc). 39 From Fig. 10b, the pHzpc for the adsorbents CeBC-A@CS, LaBC-A@CS and AlBC-A@CS is 7.1.…”
Section: Effect Of Phmentioning
confidence: 90%
“…e removal of fluoride from aqueous media using lanthanum and cerium modified mesoporous alumina (La/MA and Ce/MA) was studied, and it was found that the maximum adsorption capacity of La/MA was 26.45 mg/g, and the capacity of La/ MA was more than Ce/MA and mesoporous alumina [46]. One study showed that the fluoride removal efficiency of the mineral-substituted hydroxyapatite nanocomposite (mHAp) adsorbent is 93% [47]. Another study by Dubey et al demonstrated that the maximum adsorption of fluoride by using NPs of gamma alumina and alcoholic aluminum chloride was 23 mg/g [48].…”
Section: Nanoparticles (Nps)mentioning
confidence: 99%